PERANCANGAN MEDIA PEMBELAJARAN INTERAKTIF MATA PELAJARAN IPA KELAS VI SD BERBASIS WEBSITE - Septiana Vratiwi; Efendi Efendi; Risma Wiwita; Taufik Abdul Hasan Amrullah (JURNAL KEPEMIMPINAN DAN PENGURUSAN SEKOLAH, 2022)
The library is a center of knowledge that must be managed properly and correctly in an educational institution. SLBN 1 Linggo Sari Baganti is a school where all kinds of activities get more attention from the government, one of which is through the library. various assistance, facilities and infrastructure in the form of a collection of books are always provided. However, the operation of the library at SLBN 1 Linggo Sari Baganti is currently still managed in a conventional way. Starting from the data collection process to borrowing books is still done manually. Causing activities to be slow, inefficient and errors tend to be repeated frequently. So the Design of a Library Information System at SLBN 1 Linggo Sari Baganti Using Visual Basic 2010 Programming Language and Supported by Mysql Database is the right solution to overcome these problems. The results of the evaluation of the library system that has been designed show that the library system has features of computerized automation of data processing, transactions and the creation of important reports that have made it easier for librarians to manage the library.